Mechanical Ventilation Augments Poly(I:C)-Induced Lung Injury via a WISP1-Integrin β3-Dependent Pathway in Mice - Shuqing Jin; Zhixia Chen; Xibing Ding; Xiang Zhao; Xi Jiang; Yao Tong; Timothy R Billiar; Quan Li (BMC, 2016)
Abstract Mechanical ventilation can improve hypoxemia, but can also cause the so-called ventilator-induced lung injury (VILI). Polyinosinic:polycytidylic acid (poly(I:C)), an analogue of natural double-strand RNA virus, can induce lung inflammation. The purpose of this study was to determine whether moderate tidal volume mechanical ventilation (MTV) augments poly(I:C)-induced lung injury, and if so, the mechanism responsible for it. Two µg/g poly(I:C) were instilled intratracheally in C57BL/6J wide type (WT) mice. They were then randomized to MTV (10 ml/kg tidal volume) or spontaneous breathing. Lung tissues and bronchoalveolar lavage fluid (BALF) were collected 4 h later for various measurements. Our results showed that MTV did not cause significant injury in normal lungs, but augmented poly(I:C)-induced lung injury. The expression level of WNT-induced secreted protein 1 (WISP1) was consistent with lung injury, and the amplification of lung injury by MTV could be alleviated by anti-WISP1 antibody treatment. MTV further increased poly(I:C)-induced integrin β3 expression in the lung. We performed coimmunoprecipitation, which showed there was an interaction between WISP1 and β3. WISP1 significantly increased poly(I:C)-induced TNF-α production in macrophages isolated from WT mice, but not in macrophages isolated from β3 knockout mice. Cotreatment with WISP1 and poly(I:C) markedly increased the phosphorylation of extracellular signal-related kinase (ERK) in macrophages. Pretreating macrophages with an ERK inhibitor, U0126, dose-dependently antagonized the synergistic effect of WISP1 on poly(I:C)-induced TNF-α release. In conclusion, MTV exaggerates poly(I:C)-induced lung injury in a WISP1- and integrin β3-dependent manner, involving, at least in part, the activation of the ERK pathway. The WISP1-integrin β3 pathway could be a novel therapeutic target.